Pengaruh Fire Proofing pada Perilaku Pelat Beton Mutu Tinggi Saat Terbakar - Sulistyawati, Reni (Department of Civil Engineering, Diponegoro University, 2005)
The risk of the high-strength concrete is in line with the increase of temperature, especially for concrete slab where the surface exposure is relatively wider than beams or columns. The effort to overcome the problem has been carried out, amongst other is to cover with blanket namely fire proofing. This research is to conduct the characteristics of concrete slabs under fire exposure. Eight samples were cast with concrete having compressive strength of 52,68 MPa and were reinforced with high-strength steel having yield stress of 600 MPa. The samples which were of 60 mm thick, 600 mm wide and 1200 mm long, were equipped with reinforcement at 10 mm deep. Eight of samples were grouped into 2 samples each to represent 4 group. Each group represents the reference (type I), the ones with thicker concrete cover (type II), the ones with additional mortar cover (type III), and the ones with fire proofing product (type IV). Fire tests were conducted through all groups. and the test procedure follows the ASTM E119-88. The fire exposure was done in 30 minutes and the equivalent live load of 345 kg/m² was provided during the fire tests. Three thermocouples were also employed at different levels of depth of concrete to monitor the heat transfer in the high strength concrete and one thermocouple was used for monitoring furnace temperature. The experiment shows that the application of fire proofing product is much more efficient in reducing heat of concrete surfases. The reductions of temperature for slab type II, III, and IV are of 56,44%, 68,145%, and 85,14%. respectively. Crack spreads more evenly in the slab of type I and II. Explosive spalling happens more at the reference slab in comparison to the slab with thicker concrete cover. The deflections of slab of type I, II, III, and IV after fire exposure are of 315,92%, 319,52%, 240,84% and 73,96% in comparison to maksimum deflections.Keywords: crack, spalling, high-strength concrete, fire proofingPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3917[How to cite: Sulistyawati, R., 2005, Pengaruh Fire Proofing pada Perilaku Pelat Beton Mutu Tinggi Saat Terbakar, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 1-12]